Does Winning a Patent Race lead to more follow-on Innovation?. (13th June 2020) - Thompson, Neil C; Kuhn, Jeffrey M
Abstract: Competition between firms to invent and patent an idea, or "patent racing, " has been much discussed in theory, but seldom analyzed empirically and never at scale. This article introduces an empirical way to identify patent races, and provides the first broad-based view of them in the real world. It reveals that patent races are common, particularly in information-technology fields. The article then analyzes the effect of winning a patent race, showing that patent race winners do significantly more follow-on innovation, and their follow-on research is more similar to what was covered by the patent. (JEL CODES: O34, O32, O31)